A QUANTITATIVE ANALYSIS OF UWM STUDENTS’ AWARENESS, SATISFACTION, AND TRUST IN CAMPUS SAFETY COMMUNICATIONS - (:unkn) unknown (My University, 2024)
The Clery Act mandates that U.S. colleges and universities receiving federal funding maintain transparency for campus safety through crime reporting and communication strategies. Previous empirical studies on campus safety explored topics such as the Clery Act’s impact on campus safety and advocates’ views, the dynamics of emergency notifications, and students’ overall feelings of security and safety concerns. None of these studies tested students’ awareness, satisfaction, and trust in campus safety communications. educational environments. This study focuses on the University of Wisconsin-Milwaukee (UWM), examining students’ awareness, satisfaction, and trust in campus safety communications. Through an online survey and statistical analysis (one-sample test), this research aims to (1) ascertain whether the average level of awareness among UWM students regarding campus safety communications differs significantly from the presumed average awareness level of 3, (2) ascertain whether the average level of satisfaction among UWM students regarding campus safety communications differs significantly from the presumed average satisfaction level of 3, (3) ascertain whether the average level of trust among UWM students in the credibility of campus safety communications differs significantly from the presumed average trust level of 3, addressing gaps in existing literature and informing future campus safety policies and practices. Findings serve to better our understanding of campus safety communication and promote future research in the field.
Keywords: Campus; Communication; Education; Safety